The ghost cadet - Alphin, Elaine Marie (New York : Scholastic, 1991)
Twelve-year-old Benjy, in Virginia visiting the grandmother he has never met, meets the ghost of a Virginia Military Institute cadet who was killed in the Battle of New Market in 1864 and helps him recover his family's treasured gold watch.
P
830
P
Keywords: New Market, Battle of, New Market, Va., 1864 -- Juvenile fiction; New Market, Battle of, New Market, Va., 1864 -- Fiction; Ghosts -- Fiction; Grandmothers -- Fiction